Integrating Public Health Research and Teaching With Social Justice Activism: Lessons From 80 Years of Practice. (June 2023) - Freudenberg, Nicholas; Israel, Barbara
In this commentary, we reflect on the lessons we have learned from our successes and failures in aligning the roles of scholars and activists. Our hope is to provide insights that can guide public health students, faculty, practitioners, and activists seeking to chart their professional, political, and personal futures in today's polarized and catastrophe-burdened world. Several experiences motivate us to write this commentary now. In the last few years, inspired in part by the new activism against systemic racism sparked by the murder of George Floyd and others, growing climate emergencies, the COVID pandemic, anti-immigrant politics, increasing anti-Asian acts of violence, gun bloodshed, attacks on the right to reproductive and sexual health, resurgence of interest in worker organizing, and the ongoing quest for lesbian, gay, bisexual, transgender, and intersex (LGBTQI+) rights, we are impressed by the number of young people engaged in activism to defend and expand their rights and show that another world is possible.